2020
DOI: 10.1177/1753425920961157
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cell cytokine secretion as prognostic factor in myelodysplastic syndromes

Abstract: Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature myeloid cells that play a critical immunosuppressive role in the tumour micro-environment. Although biological research on MDSCs has made progress, the relationship between the secretion of cytokines by MDSCs and poor prognosis is not clear, and there are no criteria to measure the functional status of MDSCs. Here, we detected the mRNA expression of IL-10, IL-12, TGF-β and TNF-α in MDSCs and the levels of these cytokines in MDS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…Therefore, the S100A9–CD33 axis is an important driver of suppressive cytokine production by MDSCs in MDS BM. In line with these data, it has also been reported that the levels of IL-10 and TGFβ1 produced by Lin − /CD33 + / DR − MDSCs are increased in high-risk MDS patients, implying their possible prognostic value in patients with MDS [ 92 ]. Moreover, MDSCs could be themselves cellular sources of proinflammatory cytokines such as IL-1β [ 84 ], contributing to the inflammatory milieu, a well characterized feature of MDS [ 93 ].…”
Section: Mdscs and Immune Dysregulation In The Mdssupporting
confidence: 62%
“…Therefore, the S100A9–CD33 axis is an important driver of suppressive cytokine production by MDSCs in MDS BM. In line with these data, it has also been reported that the levels of IL-10 and TGFβ1 produced by Lin − /CD33 + / DR − MDSCs are increased in high-risk MDS patients, implying their possible prognostic value in patients with MDS [ 92 ]. Moreover, MDSCs could be themselves cellular sources of proinflammatory cytokines such as IL-1β [ 84 ], contributing to the inflammatory milieu, a well characterized feature of MDS [ 93 ].…”
Section: Mdscs and Immune Dysregulation In The Mdssupporting
confidence: 62%
“…Furthermore, MDSCs in MDS patients express a specific pattern of BM-homing chemokine receptors (CXCR4, CX3CR1) which probably contributes to their accumulation in the BM. Furthermore, in addition to their accumulation, the immunosuppressive function of MDSCs was suggested to be increased in higher-risk MDS [ 131 ]. The suppression of CD8 + T lymphocyte function was also shown to be mediated by different mechanisms such as the STA3-ARG1 or TIM3/Gal-9 pathways [ 101 , 129 ].…”
Section: Abnormal Immune Cell Repartition And/or Functions During The...mentioning
confidence: 99%
“…In addition, high-risk MDS-derived MDSCs exhibit higher activated activator of transcription (STAT)3 and C-C chemokine receptor type (CCR)2 expression, whereas STAT3 pathway targeting decreases ARG1 expression in MDSCs and partially revokes reduced expression levels of effector molecules in CD8+ T lymphocytes [155]. Thus, MDSCs may contribute to the BM microenvironment switch to an immunosuppressive environment as the MDS disease progresses [156].…”
Section: Mdscs In Myelodysplastic Syndromementioning
confidence: 99%